Javanese Cockfighting : Significance and value - Boedhihartono Boedhihartono (Journal of Tropical Ethnobiology, 2005)
This article explained the Javanese cockfighting and their significance and value. Generally, the Javanese classify the chickens according to their feature and function, each feature has a symbolical significance according to its function. In this article also discussed about the fowl, status attributes and belief, selection, breeding and preparation of fighting cocks, and cockfighting, matches, role, and regulation and cultural significance of the practice and significance of cockfighting to germ-plasm conservation. The practice of the cockfighting of the society has a great significance to the effort of maintaining the genetic variability of indigenous fowls. It motivates people with limited settlement space to actively participate in breeding different varieties of fowl and it gives opportunity to the common with a limited capital to earn extra money from breeding only a limited number of cocks. After all, the cockfighting and all its other correlating activities are forming a unity which is consciously developed by the Javanese and merit to be regarded as an art and becoming a part of the sophistication of the fowl domestication.